Bentuk Gabungan Tindak Pidana Perdagangan Anak dengan Memalsukan Data Korban (Putusan Nomor 128/Pid.Sus/PN.Mnd): Forms of Criminal Combination in the Crime of Child Trafficking by Falsifying Victim Data (Decision Number 128/Pid.Sus/PN.Mnd) - Gabriel Maria Aurelia Gagola; Maria Silvya E Wangga (Faculty of Law, Universitas Trisakti, 2024)
The combined form of crime contained in the crime of child trafficking and data falsification contained in the case of Decision No.128/Pid.sus/2021/PN.Mnd, the victims in this decision case are children aged 18 years, 15 years and 13 years and to make it easier for the perpetrator to carry out the crime of child trafficking, the perpetrator faked the KTPs of the victims who were aged 15 years and 13 years, so that the defendant's actions not only violated “Article 2 paragraph (1) of Law Number 21 of 2007 concerning the crime of trafficking in persons but also There is another criminal act, namely committing data falsification which violates Article 19 paragraph (1) of this law. The problem in this research is What is the form of combining criminal acts contained in decision case No.128/Pid.Sus/PN.Mnd? This research uses a normative juridical research type which is descriptive and analyzed qualitatively by drawing conclusions logically deductively.” From the results of this research, conclusions are drawn in the case of decision no. 128/Pid.Sus/2021/PN.Mnd There are two forms of combined crimes, namely concurrent regulations (concursus idealis) and concurrent actions (concursus realis)